THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE EDUCATIONAL PROCESS - Zuxra Bektemirova Omonjon qizi, (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
Information technologies as one of the components of an integral learning system not only open up the possibilities of variability of educational activities, its individualization and differentiation, but also allow organizing the interaction of all subjects of learning in a new way.